Academic Publishing Incentive Structures and Authorship Behaviors: A Game-Theoretic Model - Hasan Çebi Bal; Filiz Kutluay Tutar; Abdallah Abukalloub (CV. Media Digital Publikasi Indonesia, 2026)
This study examines how incentive structures in academic publishing shape authorship practices in contemporary performance-oriented academic systems. Growing reliance on publication counts, citation metrics, journal rankings, and authorship positions has made academic authorship a strategic mechanism for allocating institutional rewards. In this context, practices such as reciprocal authorship, honorary authorship, guest authorship, and strategically motivated collaboration have become increasingly visible in scholarly publishing. Drawing on rational choice theory and non-cooperative game theory, the study develops a theoretical model that conceptualizes academic authorship as a strategic interaction shaped by publication pressure, incomplete information, asymmetric monitoring, contribution costs, ethical risks, and reputational incentives. Rather than assuming that academics are purely economically motivated actors, the model treats rational choice as a stylized analytical framework for examining how institutional reward systems may alter the relative attractiveness of honest and strategic authorship practices. The model suggests that reciprocal authorship may emerge as a rational equilibrium under specific conditions, particularly when publication-related rewards are high, genuine contribution costs are substantial, monitoring mechanisms are weak, and ethical or reputational costs remain limited. At the same time, the study emphasizes that this equilibrium is conditional and may be altered by stronger transparency mechanisms, contribution disclosure systems, disciplinary norms, professional identity, and ethical enforcement. The findings suggest that problematic authorship behaviors should be understood not only as individual ethical failures but also as structurally embedded responses to institutional incentive systems. The study argues that sustainable reform requires multidimensional evaluation systems that combine contribution-based assessment, transparent disclosure, institutional accountability, and qualitative judgments of scientific quality, rather than simply replacing authorship counts with new quantitative contribution metrics.